Exploring genetic diversity and trait associations with foliar blast disease among parental lines in pearl millet [Pennisetum glaucum (L.) R Br] - Rasitha, R.; Kalaiyarasi, R.; Iyanar, K.; Senthil, N.; Johnson, I. (Journal of Phytology, 2024)
Thirty-seven pearl millet genotypes were evaluated for morphometric traits and disease incidence and severity during summer and kharif, 2022. Pooled ANOVA revealed significant variation were present in all genotypes across different season. Association studies identified high positive correlations between grain yield and traits such as single earhead weight, single ear head threshed weight, and test weight, with direct and indirect effects on grain yield through key characters. E2 (kharif – 2022) showed favourable conducive weather parameters for disease infection throughout the growing season compared to E1. The higher PCV relative to GCV for disease incidence underscores the environmental influence in disease resistance programs. Negative correlations between disease metrics and yield traits highlight blast disease’s detrimental effect on grain yield. Disease severity indirectly suggests environmental factors may enhance its impact. Disease incidence exhibited a direct negative impact on yield, supported by negative genotypic correlations. The line, PT 6679, exhibit both high yield and highly resistant to blast. Restorer lines (PT 6029, PT 6067, PT 6300, PT 6707, PT 7068) and B lines (ICMB 01666, ICMB 02777) showed promising yield attributes with high to moderate disease resistant for future breeding programs. In D2 analysis, five clusters revealed distinct genetic diversity with Clusters II and V indicating strong hybrid vigor, while Clusters IV (PT 6946, ICMB 06111) and V (ICMB 93111, ICMB 95444) excelled in disease resistance. Clusters I (PT 6029, PT 7068) and II (GMR 58) exhibited superior grain yield, particularly Cluster I, had potential restorer lines for future breeding. Clear differentiation between B and R lines underscored genetic distinctions in trait expression, validating the use of morphological data for assessing genetic diversity.